The effect of activated carbon addition on membrane bioreactor processes for wastewater treatment and reclamation – A critical review. (June 2015) - Skouteris, George; Saroj, Devendra; Melidis, Paraschos; Hai, Faisal I.; Ouki, Sabèha
Highlights: AC addition to MBRs fortify adsorption, potentially enhancing biodegradation. AC-assisted MBRs more effectively remove resistant pollutants than usual MBRs. AC addition to MBRs can retard membrane fouling and improve membrane flux. For AC-assisted MBRs, AC dosage and retention time must be carefully controlled. Frequent but low-dose AC addition may facilitate timely replenishment of spent AC. Abstract: This review concentrates on the effect of activated carbon (AC) addition to membrane bioreactors (MBRs) treating wastewaters. Use of AC-assisted MBRs combines adsorption, biodegradation and membrane filtration. This can lead to advanced removal of recalcitrant pollutants and mitigation of membrane fouling. The relative contribution of adsorption and biodegradation to overall removal achieved by an AC-assisted MBR process can vary, and "biological AC" may not fully develop due to competition of target pollutants with bulk organics in wastewater. Thus periodic replenishment of spent AC is necessary. Sludge retention time (SRT) governs the frequency of spent AC withdrawal and addition of fresh AC, and is an important parameter that significantly influences the performance of AC-assisted MBRs. Of utmost importance is AC dosage because AC overdose may aggravate membrane fouling, increase sludge viscosity, impair mass transfer and reduce sludge dewaterability.